Nutritional Security in Drylands: Fast-Track Intra-Population Genetic Improvement for Grain Iron and Zinc Densities in Pearl Millet - Govindaraj, Mahalingam; Rai, Kedar Nath; Kanatti, Anand; Rao, Aluri Sambasiva; Shivade, Harshad (Frontiers in Nutrition, 2019)
Considering the pervasive malnutrition caused by micronutrients, particularly those arising from the deficiencies of iron (Fe) and zinc (Zn), the primary focus of research in pearl millet is on biofortifying the crop with these two minerals. Pearl millet is a highly cross-pollinated crop where open-pollinated varieties (OPVs) and hybrids are the two distinct cultivar types. In view of the severe deficiency of Fe and Zn in Asia and Africa where this crop is widely consumed, crop biofortification holds a key role in attenuating this crisis. The present study included three OPVs previously identified for high-Fe and Zn density to assess the magnitude of variability and test the effectiveness of intra-population improvement as a fast-track selection approach. Large variability among the S1 progenies was observed in all three OPVs, with the Fe varying from 31 to 143 mg kg−1 and Zn varying from 35 to 82 mg kg−1. Progeny selection was effective for Fe density in all three OPVs, with up to 21% selection response for Fe density, and up to 10% selection response in two OPVs for Zn density, for which selection was made as an associated trait. Selection for Fe density had no adverse effect on grain yield and other agronomic traits. These results suggest that effective selection for Fe density in OPVs and composites can be made for these micronutrients and selection for Fe density is highly associated with the improvement of Zn density as well. These genetic changes can be achieved without compromising on grain yield and agronomic traits. Such improved versions could serve as essentially-derived varieties for immediate cultivation and also serve as potential sources for the development of parental lines of hybrids with elevated levels of Fe and Zn density. Therefore, fast-track breeding is essential to produce biofortified breeding pipelines to address food-cum-nutritional security.